Risk Ratio of Osteoporosis According to Body Mass Index, Parity, and Caffein Consumption - Limbong, Elsa Adlina; Syahrul, Fariani (Jurnal Berkala Epidemiologi, 2015)
The number of osteoporosis tends to increase in Indonesia. East Java is one of five provinces with the highest risk of osteoporosis in Indonesia. This study aims to analyze risk ratio of osteoporosis for women according to BMI, parity, and caffeine consumption. Research used observational analytic with case control design. Sample case came from women with osteoporosis who reside in surabaya and did the checkup at Dr. Soewandhie Surabaya Hospital at 2013â2014. Control sample came from non osteoporosis women who reside in surabaya and did the checkup at Dr. Soewandhie Surabaya Hospital at 2013â2014. Respondents consisted of 45 cases and 45 controls were obtained using simple random sampling method. Data was obtained from primary and secondary data. The independent variables were body mass index, parity and caffeine consumption. Analysis was done by using OR calculation on Epi Info with significance level 95% CI. The risk ratio of each variable include BMI (OR = 2,99; 95% CI = 1,16 < OR < 7,74), parity (OR = 2,72; 95% CI = 1,07 < OR < 7,01), and caffeine consumption (OR =2,41;95% CI = 0,91 < OR < 6,42. The conclusion are women who had BMI <18.5 were at risk of osteoporosis 2.99 times more than women who had BMI â¥18,5. Women who had parity â¥ 3 times were at risk of osteoporosis 2.72 times more than women who have parity < 3 times. Women who consume caffeine â¥ 2 cups/ day were at risk of osteoporosis 2.41 times more than women who consume caffeine <2 cups/day but not significant. Researcher recommend women to have normal BMI and limit the number of births to prevent osteoporosis.Keywords: risk, osteoporosis, BMI, parity, caffeine